Identification of Determinants of Customer Decisions in Choosing Savings at Digital Banks - Sinaga, Hanif Zaidan; Rahmawati, Amelia; Amelia, Anggi (Universitas Ibn Khaldun Bogor, 2023)
Abstract The development of digital banking is increasing rapidly in line with the increasing interest and number of users. Digital banking is defined as banking services using digital facilities owned by banks, carried out independently by customers to obtain information, communicate, open accounts, banking transactions, and close accounts including obtaining other information outside of banking products including financial advisors, investments, e-commerce transactions and others. The use of online banking can be influenced by factors that support choosing online banking. This study aims to analyze how customers choose LINE Bank (Hana Bank) as the digital bank used today. This research uses a quantitative method with a descriptive approach that aims to make a description, description or painting systematically, accurately about the facts, properties and relationships between the phenomena being investigated. The sampling method uses nonprobability sampling with the purpose method. The data collection technique used in this study was a questionnaire. The results of this study indicate that each questionnaire item is a determining factor in the customer's decision to choose digital savings at LINE Bank so that LINE Bank is suitable for the community as a savings account that is easy to use and easy to access because it is internet-based.